Efficiency of Early Warning Scores in Adult Emergency Department and Inpatient Populations: Overview of Reviews - Michal Pospíšil; Tereza Friessová; Tamara Skříšovská; Andrea Pokorná; Jan Maláska; Jana Rozmarinová; Alena Langaufová (Western Journal of Emergency Medicine, 2026)
Introduction: Early Warning Scores (EWS) are used to support decisions regarding triage and early intervention of patient deterioration in emergency departments (ED) and other clinical environments. We synthesized evidence from systematic reviews on the predictive performance and clinical impact of EWS and their modifications in adult in-hospital populations. Methods: We conducted and reported an overview of reviews following the Joanna Briggs Institute (JBI) methodology, PRIOR statement, and our predefined protocol. A systematic search of MEDLINE (Ovid) and Epistemonikos was performed in May 2025. Two reviewers independently screened studies, extracted data, and critically appraised systematic reviews. We included systematic reviews of adult in-hospital populations evaluating EWS as either prognostic tools for deterioration or mortality, or as interventions implemented within track-and-trigger or rapid response systems. Primary study overlap was quantified using the corrected covered area (CCA). We synthesized evidence narratively and tabularly, emphasizing ED-related data. Results: From 502 records identified, 21 systematic reviews comprising 343 primary studies were included. We identified ED-relevant evidence in 12 reviews. In ED populations, EWS demonstrated moderate-to-good discrimination for mortality and clinical deterioration (National EWS area under the receiver operating characteristic curve (AUROC) values: 0.88 for 24-hour mortality, 0.86 for 48-hour mortality). Across ED and mixed acute-care cohorts, Early Warning Scores also showed fair performance for predicting ICU admission and composite adverse outcomes (AUROC ~0.70–0.75). In sepsis-focused analyses relevant to ED populations, quick Sequential Organ Failure Assessment (qSOFA) demonstrated low sensitivity but high specificity for 28/30-day mortality (sensitivity 0.41, 95% CI, 0.24–0.62; specificity 0.88, 95% CI, 0.81–0.92). The SOFA score showed high sensitivity and moderate specificity for in-hospital mortality (sensitivity 0.89, 95% CI, 0.88–0.90; specificity 0.69, 95% CI, 0.68–0.69). Evidence on the clinical impact of EWS implementation in ED and other emergency settings was limited and heterogeneous. Conclusion: In EDs, Early Warning Scores support early risk stratification and identification of patients at risk of deterioration, particularly for short-term mortality and escalation of care. Their impact on patient-important outcomes remains uncertain. Early Warning Scores should complement clinical judgment, triage systems, and structured escalation protocols. They should not be a standalone tool. Future research should prioritize standardized thresholds, transparent reporting, and rigorous comparative and implementation studies defining the role of EWS in emergency care.